Jehovah's Witnesses and blood transfusion refusal: a narrative review of ethical and legal aspects - Ferreira, Chrystiano de Campos (2025)
Introduction: Jehovah's Witnesses, a religious group founded in the late 19th century by Charles Russell, have as one of their core beliefs the rejection of practices they consider incompatible with biblical teachings, notably the refusal of blood transfusions. Based on a literal interpretation of biblical passages such as Acts 15:29 and Leviticus 17:10-14, this practice raises ethical, legal, and social implications, especially in medical contexts where blood transfusions are often essential to saving lives. This study analyzes the ethical and legal aspects of this refusal, focusing on the relationship between religious freedom, individual autonomy, and the right to health. Methodology: The research was conducted through a narrative literature review, addressing scientific articles and jurisprudence from the Federal Supreme Court (STF) and the Superior Court of Justice (STJ). Results: During the search, 248 articles were found, of which 16 were selected, along with relevant jurisprudence. Discussion: The refusal of blood transfusion, supported by biblical interpretations, represents an ethical dilemma, especially in life-threatening situations, when the rights to autonomy and health conflict. The analysis revealed that Jehovah's Witnesses base their refusal on passages that prohibit the consumption of blood. The study also discussed Brazilian jurisprudence, which has prioritized the preservation of life, often to the detriment of religious freedom, as shown in decisions authorizing transfusions against the patient's will. The recent decision by the STF, recognizing the right of adult and capable Jehovah's Witnesses to refuse transfusions with viable alternatives, marks progress in protecting religious autonomy. However, for minors, the principle of the best interest of health prevails. Conclusion: It is concluded that, despite legislative progress, it is necessary to balance the protection of religious freedom with the preservation of health and life, ensuring viable medical alternatives.